2022
DOI: 10.3390/su142114136
|View full text |Cite
|
Sign up to set email alerts
|

Rural Living Environment Governance: A Survey and Comparison between Two Villages in Henan Province of China

Abstract: Rural living environment governance is an issue of great importance in global economic development. It is also a significant facet of the rural revitalization strategy pursued by the Chinese government. Henan Province is a major agricultural province in the inland Central Plains region and is one of the most populous provinces in China. In this study, we take two villages in the underdeveloped areas of Henan Province in central China as case studies. We use field investigations and in-depth interviews to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Using an endogenous switching regression (ESR)model and linking a global ACE database to a global multi-regional input-output (MRIO) model [29,30]. Developing an assessment index system and two case studies that provides economic, social, and environmental advantages, as well as scientifically examining the function and mechanism of digital economy development on high-quality agricultural growth [31,32]. Using the SBM-DDF-Linebarger method to measure China's agricultural green total factor productivity (AGTFP) and agricultural labor surplus [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using an endogenous switching regression (ESR)model and linking a global ACE database to a global multi-regional input-output (MRIO) model [29,30]. Developing an assessment index system and two case studies that provides economic, social, and environmental advantages, as well as scientifically examining the function and mechanism of digital economy development on high-quality agricultural growth [31,32]. Using the SBM-DDF-Linebarger method to measure China's agricultural green total factor productivity (AGTFP) and agricultural labor surplus [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have shown that some regions are affected by various factors such as geographical location, regional culture, and ideology. There are many weak links in environmental management, such as little village planning (Zeng, 2021), insufficient human resources and technical support (Wang & Hu, 2021), unbalanced supply and demand structures for infrastructure and public services (Ma & Liu, 2020), and The motivation of villagers to improve the village is insufficient (Xiao et al, 2022). Rural human settlements and rural tourism are related to farmers' lives.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%